2023
DOI: 10.1093/mmy/myad126
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis and thematic review of Candida pathogenesis: Fundamental omics to applications as potential antifungal drugs and vaccines

Si Jie Lim,
Noor Dina Muhd Noor,
Suriana Sabri
et al.

Abstract: Invasive candidiasis caused by the pathogenic Candida yeast species has resulted in elevating global mortality. The pathogenicity of Candida spp. is not only originated from its primary invasive yeast-to-hyphal transition; virulence factors (transcription factors, adhesins, invasins, and enzymes), biofilm, antifungal drug resistance, stress tolerance, and metabolic adaptation have also contributed to a greater clinical burden. However, the current research theme in fungal pathogenicity could hardly be delineat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 201 publications
0
2
0
Order By: Relevance
“…No bibliometric studies were found on this topic. Most similar studies are focused on aroma therapy [12,13] and antimicrobial effects [14][15][16]. Moreover, several studies were solely dedicated to examining the properties of individual essential oils [17,18].…”
Section: Thematic Mapmentioning
confidence: 99%
“…No bibliometric studies were found on this topic. Most similar studies are focused on aroma therapy [12,13] and antimicrobial effects [14][15][16]. Moreover, several studies were solely dedicated to examining the properties of individual essential oils [17,18].…”
Section: Thematic Mapmentioning
confidence: 99%
“…However, there is currently a paucity of bibliometric research in the field of orthopedic biofilms, although some bibliometric studies have been conducted on biofilms related to wound healing, 10 biofilm eradication, 8 and microbial resistance. 11 Therefore, this study aimed to employ bibliometric visualization analysis based on bibliometrix to analyze current trend and hotspots in orthopedic biofilm research.…”
Section: Introductionmentioning
confidence: 99%